2011
DOI: 10.1007/s00586-011-1828-0
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous intracranial hypotension due to intradural thoracic osteophyte with superimposed disc herniation: report of two cases

Abstract: Spontaneous intracranial hypotension (SIH) is a clinical syndrome in which absolute or relative hypovolemia of the cerebrospinal fluid (CSF) results in various neurological symptoms. The etiology of spontaneous CSF leaks often remains unknown. However, it is believed that the most common cause is the fragility of spinal meninges at the level of radicular nerve root sleeve. These tears can be spontaneous (primary) or secondary. Spinal pathologies can cause this tear with resultant CSF leak and SIH, which includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…51,52 Rarely, the dura mater may be physically eroded by spinal osteophytes. 8,22,66,68 Intracranial hypotension presenting as severe depression of mental status or coma is unusual but has been reported multiple times in the literature (Table 1).…”
Section: Jns112030) Abstract • Coma • Cerebrospinal Fluid Leak • Epmentioning
confidence: 99%
“…51,52 Rarely, the dura mater may be physically eroded by spinal osteophytes. 8,22,66,68 Intracranial hypotension presenting as severe depression of mental status or coma is unusual but has been reported multiple times in the literature (Table 1).…”
Section: Jns112030) Abstract • Coma • Cerebrospinal Fluid Leak • Epmentioning
confidence: 99%
“…It can be observed that 77 % of these cases were caused by trauma of varying aetiologies and only two (4.5 %) of the cases were described as subsequent to post-operative thoracic disc resection [2,9,[14][15][16][17]. Recently, two cases of spontaneous thoracic CSF leakage in the presence of thoracic disc hernias were described [18]. It must be concluded that subarachnoid-pleural fistula subsequent to an anterior resection of thoracic disc is a very rare entity.…”
Section: Epidemiology Pathology and Rationale For Treatmentmentioning
confidence: 99%
“…While dural tear may occur anywhere along the spinal axis, laceration, and subsequent CSF leakage at the nerve root sleeve may be relatively rare: PubMed search using the keywords IC and root sleeve yielded only seven previous cases [ Table 1 ]. [ 15 16 17 18 19 20 21 ] As shown in Figure 2b , reconstructed coronal view of the CT myelogram may particularly be useful to identify CSF leakage occurring at the root sleeve.…”
Section: Discussionmentioning
confidence: 99%
“…Year of publication Spinal level Pleasure et al [15] 1998 Lumbar Schievink and Jacques [16] 2003 Cervical Watanabe et al [17] 2009 Thoracic Ohtonari et al [18] 2009 Lumbar Cheshire and Wharen [19] 2009 Cervical Hasiloglu et al [20] 2012 Thoracic/thoracic Tontisirin et al [21] 2018 Thoracic Present case 2018 Thoracic…”
Section: Authormentioning
confidence: 99%